Vascular Smooth Muscle Cells Express the Transcriptional Corepressor NAB2 in Response to Injury - Silverman, Eric S. (American Society for Investigative Pathology, 1999)
The early growth response 1 (Egr-1 or NGFI-A) gene product is a zinc finger protein transcription factor which has been implicated in the regulation of genes differentially expressed during the development of vascular disease. Egr-1 activity is regulated by alterations in the amount of protein, as well as protein-protein interactions with positive and negative transcriptional cofactors. NGFI-A-binding protein 2 (NAB2) is an example of a negative transcriptional cofactor capable of binding directly to Egr-1 and repressing Egr-1-mediated transcription. In this study, we show that NAB2 is rapidly and transiently expressed in vascular smooth muscle cells (VSMC) in response to the model agonist phorbol 12-myristate 13-acetate (PMA). This induction occurs at the protein as well as mRNA level, and the time course of induction trails closely behind that of Egr-1. NAB2 expression in VSMC is capable of inhibiting Egr-1 dependent gene expression in response to either PMA or fibroblastic growth factor-2 (FGF-2). In an in vivo model of mechanical arterial injury NAB2 levels also increase transiently in VSMC at a time when Egr-1 is elevated. It is possible that NAB2 is part of a negative-feedback mechanism which serves to down-regulate Egr-1-mediated gene transcription in injured VSMC.